A study for correlation of demographic data, chief complaints and risk factors with periodontitis - Vinchurkar, Urjita; Piludariya, Anvi G.; Modi, Palak R.; Mistry, Yogita D.; Parmar, Gunvant; Mullan, Summaiya A. (International Journal Of Community Medicine And Public Health, 2023)
Background: Periodontal disease, ever since the days of hippocrates has crippled the survival of human dentition. As a quiescent disease most of the time, periodontal disease presents mainly a chronic or asymptomatic chief complaint. In its most common form, periodontal disease generally is considered to be a painless process unless it reaches severe stages. For this reason, it often is overlooked by patients and dentists in early stages, especially when inflammation is not obvious. The aim of this study was to determine the most common chief complaints of chronic periodontitis patients to assess public awareness about this disease symptom, distribution of these chief complaints among males & females and their correlation with age and some of periodontal parameters. Methods: The data of patients include chief complaint of the patients, age-sex, patient’s education level, systemic and oral health status, smoking, tobacco and gutka chewing habits were collected. The examiner also collected information related to the toothbrushing frequency of each patient. Results: Total samples testing in the study were 100 (n=100). Out of which majority samples were female patients. Maximum samples were received from age group of 51-60 years. Major pre-disposing factor is Tobacco and Gutka Chewing. Majority of chief complaint was mobility of teeth. Conclusions: 51 years to 60 years of age group with higher number of females and tobacco chewer have higher incidence of periodontitis with major chief complaint of mobility of teeth. These patients are brushing once in a day.